Comparison of the Evaluation of Combination of Ultrasonography of the Reproductive Tract With Hormone Administration on Dairy Cow Fertility - Wang, Bingke; Xiao, Jinbang; Ma, Yongjie; Gao, Chuxi; Li, Hanbing; Jia, Yonghong; Jin, Yaping; Lin, Pengfei (Frontiers in Veterinary Science, 2022)
Further optimization of reproduction management programs in dairy cows is contemporary research topic. In this context, our study aimed to compare a hormone program, named “uterus-ovary monitoring and classified use of hormone program” (M+C), with the Pre-OvSynch program. The M+C was based on regular application of B-mode ultrasonography during a voluntary waiting period to monitor the uterus and ovaries, while using various treatments under different conditions. Results of the 30–33-day and 60-day pregnancy/artificial insemination after the first AI of M+C were significantly better than the Pre-OvSynch (P < 0.05). The pregnancy rates within 180 days in milk after M+C was significantly higher than that after Pre-OvSynch (P < 0.05). The total number of inseminations used for M+C was significantly lower than that for Pre-OvSynch (P < 0.01). The number of open days was fewer after M+C than after the Pre–OvSynch throughout the experimental period with highly significant differences (P < 0.01). In summary, the use of M+C enhances reproductive benefits and reduces the need for hormone drugs among cows.